Advanced Therapeutic Approaches Based on Small Extracellular Vehicles (sEVs) For the Regeneration of Spinal Cord Injuries - Anjum A; Chan AML; Hussain HB; Lokanathan Y (International Journal of Nanomedicine)
Anam Anjum,1,2 Alvin Man Lung Chan,2,3 Hafiz Bilawal Hussain,4 Yogeswaran Lokanathan2,5 1Department of Neurosurgery, University of Maryland School of Medicine, Baltimore, MD, 21201, USA; 2Department of Tissue Engineering and Regenerative Medicine, Faculty of Medicine, Universiti Kebangsaan Malaysia, Kuala Lumpur, 56000, Malaysia; 3My CytoHealth Sdn. Bhd, Lab 6, DMC Level 2, Hive 5, Taman Teknologi MRANTI, Bukit Jalil, 57000, Malaysia; 4Department of Orthopaedic Surgery and Traumatology Unit-1, Jinnah Hospital Lahore, Jinnah Hospital, Allama Iqbal Medical College, Lahore, 54550, Pakistan; 5Advance Bioactive Materials-Cells UKM Research Group, Universiti Kebangsaan Malaysia, Bangi, 43600, MalaysiaCorrespondence: Yogeswaran Lokanathan, Email lyoges@hctm.ukm.edu.myAbstract: Spinal cord injury (SCI) is severe damage to part of the central nervous system (CNS) that can result in impaired sensory and motor function, significantly impacting the quality of life for patients and creating a substantial economic burden on society. The process of SCI involves both primary and secondary injury, with the latter being a series of heightened responses triggered by the initial damage. The complex nature of SCI’s pathological mechanisms has made it challenging to develop effective treatment strategies in clinical settings. Small extracellular vesicles (sEVs) are membrane-bound vesicles with a size range of ≤ 200 nm, released from cells into extracellular spaces. These vesicles are heterogeneous and can originate from various intracellular compartments, including endosomal and non-endosomal sources. A growing body of evidence points to the potential of sEVs in repairing SCI. This review explores the preparation, functions, routes of administration, advantages, challenges, and advanced therapies for sEVs. It also examines the mechanisms through which various types of sEVs can promote healing in SCI and assesses the effectiveness of combining sEVs with other treatment approaches. Furthermore, the review discusses the opportunities and obstacles associated with using sEVs to repair SCI.Keywords: neuroinflammation, mesenchymal stem cells, MSC, angiogenesis, glial scar formation, nerve regeneration